NARASI EMANSIPASI PEREMPUAN DALAM AL-QUR’AN: TELAAH HERMENEUTIK DAN FILSAFAT GENDER TERHADAP AYAT-AYAT KESETARAAN - Aisyah Nur; Al Fiqri Ardiansyah; Mei Arina Ilmi AS (Jurnal Ilmiah Mahasiswa Raushan Fikr, 2025)
This study reexamines Qur’anic verses on women through philosophical hermeneutics and critical gender philosophy to construct an emancipatory narrative affirming equality and freedom in Islam. Key verses such as Q.S. Al-Ahzab [33]:35, Al-Nisa [4]:1, [4]:34, Al-Tawbah [9]:71, Al-Hujurat [49]:13, and Al-Isra [17]:70 are analyzed using library research, drawing from classical and contemporary tafsir and critical theorists like Gadamer, Ricoeur, Butler, and Fraser. Concepts such as fusion of horizons, distanciation, performativity, and recognition justice guide a rereading that challenges patriarchal interpretations. The findings affirm that the Qur’an provides a strong ethical and theological basis for emancipatory theology, rooted in rahmah (compassion), karāmah insāniyyah (human dignity), and ta’dīl (justice). Women are positioned as autonomous moral agents rather than passive legal subjects. A justice-based reinterpretation is thus essential for building a transformative Islamic paradigm aligned with contemporary gender equality discourses.